2021
DOI: 10.7150/jca.62309
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis reveals sophisticated metabolic alteration and identifies FMNL1 as a prognostic marker in clear cell renal cell carcinoma

Abstract: In this study, we have undertaken the whole proteomic analysis and got a better understanding of biological processes involved in the development and progression of ccRCC. We hope promising biomarkers can be uncovered to facilitate early diagnosis, predict the prognosis and progression, more importantly, to be applied as potential therapeutic targets. Experimental design: Fresh frozen tissue samples were surgically resected from patients with local or locally advanced ccRCC. Trypsin digested proteins were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…FMNL1 encodes a formin-related protein that is implicated in morphogenesis, cytokinesis and cell polarity. FMNL1 has been reported to act as a prognostic factor in multiple tumors (Chen et al, 2018;Higa et al, 2019;Ma et al, 2021); however, the role of FMNL1 in colon cancer has not been investigated yet. Our findings provided new clues for the crucial role of FMNL1 as a potential target for KRAS-mutant colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…FMNL1 encodes a formin-related protein that is implicated in morphogenesis, cytokinesis and cell polarity. FMNL1 has been reported to act as a prognostic factor in multiple tumors (Chen et al, 2018;Higa et al, 2019;Ma et al, 2021); however, the role of FMNL1 in colon cancer has not been investigated yet. Our findings provided new clues for the crucial role of FMNL1 as a potential target for KRAS-mutant colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…FMNL1 expression was shown to be upregulated in a variety of cancers, and this upregulation aided cell invasiveness. FMNL1 could intensify the aggressiveness of tumor cells intensify the aggressiveness of tumor cells through a variety of ways, in addition to facilitating cytoskeletal remodeling [ 23 ]. FMNL1 increased cell aggressiveness in nasopharyngeal cancer by epigenetically upregulating MTA1.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we discovered that high FMNL1 expression predicted a better prognosis in HCC. Previous studies have linked high FMNL1 expression to a poor prognosis in a variety of cancers, including clear cell renal cell carcinoma [ 23 ], gastric cancer [ 9 ], and glioblastoma [ 28 ]. FMNL1 was found to promote T cell and macrophage migration in the previous studies [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Notably, the TCGA analysis of ccRCC revealed that metabolic changes play a crucial role in the evolution of ccRCC. [14,19,20] A study and its subsequent analysis revealed a correlation between poorer survival of ccRCC patients and the increased expression of genes related to the pentose phosphate pathway and fatty acid synthesis pathway, as well as the decreased expression of genes related to the TCA cycle. [21] The significance of FA metabolism in cancer cell functioning, as well as the Warburg effect (perturbed glucose metabolism) and altered amino acid metabolism (specifically glutamine metabolism), is gaining recognition.…”
Section: Introdutionmentioning
confidence: 99%